Food Safety Toolkit - International Finance Corporation (International Finance Corporation, Washington, DC, 2018)
The IFC Food Safety Toolkit is designed to help companies in developing markets reduce a risk in growing a sustainable food business: meeting the ever-increasing demands, needs, expectations and trust of customers, wholesalers, retailers, government food safety regulators, and consumers. The Toolkit was developed by IFC with food industry help and expertise. It is based on HACCP principles of foodstuff hygiene, and best industry practices and standards. The Toolkit provides companies with the know-how to develop, implement and maintain a modern food safety management system based on the principles of the Hazard Analysis Critical Control Points system (HACCP). The Toolkit helps companies to identify gaps in their existing practices and develop more efficient food safety system. Specifically, companies can: apply the Toolkit in any process regardless of production facility size, location and food safety sophistication; develop systemic science-based approaches to food safety management; benchmark their own food safety system against the best international practices; use the Toolkit as simple and practical self-service tool, replicating it to all production lines as necessary; tailor the templates in accordance with their needs. The Toolkit consists of seven modules with adjustable templates for food safety documentation and procedures.